KONSTRUKSI PERTIMBANGAN HAKIM DALAM PENERAPAN PRINSIP INDIVIDUALISASI PIDANA DEMI MEWUJUDKAN PERLINDUNGAN ANAK - C Maya Indah (Masalah-Masalah Hukum, 2014)
The penal individualization in juvenile justice is a main approach for reaching protection for the child.The judge should has a capacity for interpreting a characteristic inherent in the handling of juvenile offender to achieve juvenile justice in a legal,sosio and philosophy perspective .The socio legal research approach was used as the research method.The study concluded that in a empirical fact ,the concideration of the judge tend to eliminate the best interest for the child principle as a basic rights